Effects of Alternate Wetting and Drying Irrigation Regime and Nitrogen Fertilizer on Yield and Nitrogen Use Efficiency of Irrigated Rice in the Sahel - Djaman, K.; Mel, V.C.; Diop, L.; Sow, A.; El-Namaky, R.; Manneh, B.; Saito, Kazuki; Futakuchi, K.; Irmak, S. (MDPI, 2018)
The objectives of this study were to investigate water saving strategies in the paddy field and to evaluate the performance of some of the newly released rice varieties. Field experiments were conducted at Fanaye in the Senegal River Valley during two rice growing seasons in 2015. Three irrigation regimes ((i) continuous flooding, (ii) trigging irrigation at soil matric potential (SMP) of 30 kPa, (iii) trigging irrigation at SMP of 60 kPa) were tested in an irrigated lowland rice field. Irrigation regimes (ii) and (iii) are alternate wetting and drying (AWD) cycles. Four inbred rice varieties (NERICA S-21, NERICA S-44, Sahel 210 and Sahel 222) and one hybrid rice (Hybrid AR032H) were evaluated under five nitrogen fertilizer rates (0, 50, 100, 150 and 200 kg N ha−1). The results showed that rice yield varied from 0.9 to 12 t ha−1. The maximum yield of 12 t ha−1 was achieved by NERICA S-21 under AWD 30 kPa at 150 kg N ha−1. The AWD irrigation management at 30 kPa resulted in increasing rice yield, rice water use and nitrogen use efficiency and reducing the irrigation applications by 27.3% in comparison with continuous flooding. AWD30 kPa could be adopted as a water saving technology for water productivity under paddy production in the Senegal River Middle Valley. Additional research should be conducted in the upper Valley, where soils are sandier and water is less available, for the sustainability and the adoption of the irrigation water saving practices across the entire Senegal River Valley.